2004
DOI: 10.21273/hortsci.39.7.1611
|View full text |Cite
|
Sign up to set email alerts
|

Tergitol TMN-6 for Thinning Peach Blossoms

Abstract: This study was conducted to determine efficacy of Tergitol TMN-6 in thinning peach blossoms. A pretest was conducted and demonstrated no difference between TMN-6 and TMN-10 in efficacy when applied at full bloom or petal fall and at rates of 20 and 40 mL·L-1. In the main test, Tergitol TMN-6 was sprayed once at 10, 20, or 30 mL·L-1 at full bloom or petal fall and compared to an unsprayed control for 3 years. Tergitol caused widespread necrosis of flower parts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…Three years of research on chemical blossom thinners demonstrated that although the treatments often increased peach fruit size, they were inconsistent in reducing follow-up hand thinning requirement. These results are similar to reports from other peach producing regions (Byers, 1999;Fallahi et al, 2006;Klein and Cohen, 2000;Osborne et al, 2005;Wilkins et al, 2004).…”
supporting
confidence: 91%
“…Three years of research on chemical blossom thinners demonstrated that although the treatments often increased peach fruit size, they were inconsistent in reducing follow-up hand thinning requirement. These results are similar to reports from other peach producing regions (Byers, 1999;Fallahi et al, 2006;Klein and Cohen, 2000;Osborne et al, 2005;Wilkins et al, 2004).…”
supporting
confidence: 91%
“…Fallahi et al [13] reported that Tergitol TMN-6 at the rate of 5 mL•L −1 , applied at 75% to 85% bloom, reduced fruit set in peaches under conditions of southern Idaho, USA. Wilkins et al [14] reported that Tergitol TMN-6 effectively reduced fruit set in "Fireprince" peach under climatic conditions of Clanton, Alabama. In that report, there was no difference in thinning response at full bloom or petal fall, suggesting a wide window of efficacy for this chemical.…”
Section: Introductionmentioning
confidence: 99%
“…The surfactant, Tergitol-TMN-6, significantly reduced fruit set and increased fruit size in 'Empress' plums at various rates (7.5 and 12.5 mL · L -1 ) (Fallahi et al, 2006). Tergitol-TMN-6 is effective over a wide range of phenological stages from full bloom to petal fall, which allows for a longer window of application (Wilkins et al, 2004). The current recommendation for stone fruit is to apply Tergitol-TMN-6 at 75% to 80% full bloom at 7.5-12.5 mL · L -1 (Fallahi et al, 2006), but in South Africa, blossom thinners have not been very successful.…”
mentioning
confidence: 99%